On the Performance of LTE Downlink Scheduling Algorithms: A Case Study on Edge Throughput - Deniz, Coskun; Uyan, O. Gokhan; Gungor, Vehbi Cagri (Elsevier, 2018)
Radio resource allocation is a crucial task in the LTE networks. To increase the overall user experience, an efficient radio resource allocation algorithm should be utilized. In this work, a new scheduling algorithm has been proposed to increase the edge throughput without sacrificing system throughput. Comparative performance results indicate that the proposed scheduler increases the edge throughput and fairness while limiting degradation in the cell throughput between 0 to 2 percent with respect to the other schedulers.
Keywords: LTE; Scheduling; Resource Allocation; Radio Resource Management